The Use of Technology-Based Interactive Media in Islamic Religious Education Learning for Class VII C at Ma'arif 1 Metro Middle School and Its Implications for Students' Religious Values - Aprilian Sarifudin; Masrurotul Mahmudah; Sayyidul Abrori (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the planning, implementation, and evaluation of interactive technology-based media in Islamic Religious Education (PAI) learning at SMP Ma’arif 1 Metro and to examine its implications for students’ internalization of religious values. This research employs a qualitative descriptive field approach. Data were collected through observation, in-depth interviews with PAI teachers and seventh-grade students, and documentation. The findings indicate that interactive media such as animated videos, multimedia presentations, and digital quizzes (Quizizz and Kahoot) enhance students’ engagement, motivation, and conceptual understanding. More importantly, the use of interactive media supports the internalization of religious values through three stages: moral knowing, moral feeling, and moral action, as proposed by Thomas Lickona. Students demonstrate improved understanding of values such as honesty, responsibility, and tolerance, accompanied by reflective attitudes and practical application in classroom activities. However, the implementation still faces challenges, including limited technological infrastructure and varying levels of teachers’ digital competence. This study concludes that interactive technology-based media can serve as an effective pedagogical tool in strengthening both learning quality and religious character formation when supported by proper pedagogical guidance